Probing the methodology of Avicenna's epistemic theories - Masouleh, Abbas Kharabi; Mamat, Mohd Zufri; Hasbullah, Maisarah (Primrose Hall Publishing Group, 2019)
In the present research, the aim was to examine some of the metaphysical foundations of knowledge from the view point of Avicenna whose theories of knowledge were influentially echoed in the epistemic theories in the Islamic world and the next schools of thought. The main problem with the statement of current research is a critical question of whether Avicenna's metaphysical foundations are capable of forming a representative operation for our knowledge that is accurately representing the external world. If his metaphysical foundations fail to justify the fact that our knowledge represents the real world as it is, the metaphysical foundations of his epistemology, in spite of his realism, would inevitably slip into a fundamental gap between the known-object and the knower-subject. Such research on the principles of epistemology of Avicenna who is one of the pioneers of major thought stream in Islamic philosophy i.e. Peripatetic philosophy, can open up new perspectives for further systematic research on epistemic aspects in his doctrine. © 2019, Primrose Hall Publishing Group.